2023
DOI: 10.3390/ijms241210102
|View full text |Cite
|
Sign up to set email alerts
|

Activity of FAAH-Inhibitor JZP327A in an Experimental Rat Model of Migraine

Abstract: Increased anandamide levels via fatty acid amide hydrolase (FAAH) inhibition can decrease the pronociceptive responses and inflammatory mediators in animal models of migraine. Here, we profile the pharmacological activity of the FAAH inhibitor JZP327A, a chiral 1,3,4-oxadiazol-2(3H)-one compound, in the mediation of spontaneous and nocifensive behaviour in the animal models of migraine based on nitroglycerin (NTG) administration. JZP327A (0.5 mg/kg, i.p.) or vehicle was administered to male rats 3 h after NTG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Nonetheless, in both experimental paradigms, the FAAH inhibitor proved to be able to reduce the IoN-CCI-induced upregulation of the pain neuropeptide CGRP and proinflammatory cytokines TNF-alpha and IL-1beta and to increase the anti-inflammatory cytokine IL-10 in trigeminal-related areas. The present findings are consistent with previous studies in which FAAH inhibitors were able to alter the gene expression of pain and inflammatory mediators [33][34][35][36][37][38]. However, based on the discrepancies observed in these two different experimental settings, it appears that changes in gene expression of the mediators evaluated in this study are not directly associated with mechanical pain, thus suggesting that other signalling pathways and mediators are involved.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, in both experimental paradigms, the FAAH inhibitor proved to be able to reduce the IoN-CCI-induced upregulation of the pain neuropeptide CGRP and proinflammatory cytokines TNF-alpha and IL-1beta and to increase the anti-inflammatory cytokine IL-10 in trigeminal-related areas. The present findings are consistent with previous studies in which FAAH inhibitors were able to alter the gene expression of pain and inflammatory mediators [33][34][35][36][37][38]. However, based on the discrepancies observed in these two different experimental settings, it appears that changes in gene expression of the mediators evaluated in this study are not directly associated with mechanical pain, thus suggesting that other signalling pathways and mediators are involved.…”
Section: Discussionsupporting
confidence: 92%
“… 181 JZP327A (IC 50 = 11 nM), synthesized using 1,3,4-oxadiazol-2-ones as a scaffold, is a highly selective, slowly reversible FAAH inhibitor 182 with good analgesic effects. 183 FAAH inhibitors developed on the basis of carbamates also exhibit good selectivity, reversibility, water solubility and some neuroprotective effects. 184 …”
Section: Aea Hydrolase Faah Inhibitors In Treatment For Anxietymentioning
confidence: 99%
“…181 JZP327A (IC 50 = 11 nM), synthesized using 1,3,4-oxadiazol-2-ones as a scaffold, is a highly selective, slowly reversible FAAH inhibitor 182 with good analgesic effects. 183 FAAH inhibitors developed on the basis of carbamates also exhibit good selectivity, reversibility, water solubility and some neuroprotective effects. 184 Three-dimensional quantitative structure-activity relationship (3D-QSAR) model, which can better represent the structure-activity relationship of ligand-enzyme interaction and help to develop more effective compounds, has been widely used in FAAH inhibitor development.…”
Section: Structural Modifications Based On Lead Compoundsmentioning
confidence: 99%
“…The authors of recent studies have identified several potential targets, including enzymes, ion channels, and signaling pathways, each of which contribute uniquely to our understanding of migraine and offer new opportunities for therapeutic intervention [88,[99][100][101][102]. Three papers delve into the specifics of these experimental models and therapeutic targets, providing a thorough overview of current progress and future directions in migraine research [69][70][71].…”
Section: Experimental Models and Therapeutic Targetsmentioning
confidence: 99%
“…Greco et al investigated the potential therapeutic benefits of targeting the endocannabinoid system in the context of migraine pathophysiology [69]. Utilizing a male rat model, the authors examined the effects of trigeminal hyperalgesia using AKU-005, a dual fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) inhibitor.…”
Section: Dual Fatty Acid Amide Hydrolase (Faah)/monoacylglycerol Lipa...mentioning
confidence: 99%